2009
DOI: 10.1007/s00710-009-0092-z
|View full text |Cite
|
Sign up to set email alerts
|

Rutile occurrence and trace element behavior in medium-grade metasedimentary rocks: example from the Erzgebirge, Germany

Abstract: Metamorphic textures in medium-grade (~500-550°C) metasedimentary rocks from the Erzgebirge give evidence of prograde rutile crystallization from ilmenite. Newly-crystallized grains occur as rutile-rich polycrystalline aggregates that pseudomorph the shape of the ilmenites. In-situ trace element data (EMP and SIMS) show that rutiles from the higher-grade samples record large scatter in Nb content and have Nb/Ti ratios higher than coexisting ilmenite. This behavior can be predicted using prograde rutile crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 33 publications
(43 reference statements)
0
18
0
2
Order By: Relevance
“…On the other hand, the breakdown of detrital rutile to titanite during prograde metamorphism (Otago Province, New Zealand) has been shown to release significant amounts of W (Cave et al, 2015), later incorporated in scheelite disseminated in Otago Schist and in orogenic gold veins (Cave et al, 2016). More generally, breakdown of Fe-Ti oxides is common during diagenetic, metamorphic and hydrothermal reactions (Morad and Aldahan, 1986;Luvizotto et al, 2009;Rabbia et al, 2009), a process that can redistribute metals at a regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the breakdown of detrital rutile to titanite during prograde metamorphism (Otago Province, New Zealand) has been shown to release significant amounts of W (Cave et al, 2015), later incorporated in scheelite disseminated in Otago Schist and in orogenic gold veins (Cave et al, 2016). More generally, breakdown of Fe-Ti oxides is common during diagenetic, metamorphic and hydrothermal reactions (Morad and Aldahan, 1986;Luvizotto et al, 2009;Rabbia et al, 2009), a process that can redistribute metals at a regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that hydrothermal solutions and metamorphic fluids are capable of introducing incompatible elements in the alteration system of a chromitite, giving rise to the formation of exotic accessory minerals, such as monazite, galena, bismuthinite, and antimony that normally do not occur in unaltered chromitites [13,14]. In a number of contributions [15][16][17][18] it has been shown that certain trace elements can be successfully used to evaluate the crystallization temperature of rutile, as well as the behavior of the mineral under different metamorphic reactions. Likewise, trace element concentrations in zircon can be used to identify its geochemical signature and, therefore, probable source rock.…”
Section: Introductionmentioning
confidence: 99%
“…The divider here is taken from Triebold et al () and indicates that the vast majority of rutile were derived from metapelites. Published rutile data from Zack et al () and Zack, Moraes, & Kronz (2004a) and Luvizotto et al () are shown for comparison; metamafic rutile from the Catalina schist in California has unusually high Nb and low Cr, but all other rutile plots in the correct zones. (b) Rutile that was derived from the metamafic rocks is characterized by Nb less than 600 ppm.…”
Section: Resultsmentioning
confidence: 95%